Genetic analysis suggests a long and largely isolated evolutionary history of plum pox virus strain D in Turkey. (14th November 2019) - Gürcan, K.; Teber, S.; Candresse, T.
Abstract : Plum pox virus (PPV) strain D is globally distributed and causes serious losses in stone fruits in over 40 countries. Here, full‐length genomic sequences were analysed for 44 PPV‐D isolates from all regions of Turkey, together with partial sequences for a larger number of isolates. PPV‐D isolates from Turkey are similar to other PPV‐D isolates in all major genomic features. However, the majority of Turkish PPV‐D isolates form separate phylogenetic clusters from all other isolates and show a geographical clustering tendency, suggestive of limited movement between regions. In particular, PPV‐D isolates from Thrace and Central Anatolia formed a monophyletic sister cluster to the cluster that includes all previously known PPV‐D isolates. Two isolates with strong evidence of recombination with the PPV‐T strain were identified, together with two isolates with weaker evidence for intra‐D strain recombination. The genetic diversity of PPV‐D was found to be particularly high in Turkey (0.017 ± 0.001%), close to that observed for PPV‐D world diversity once the over‐represented isolates from Japan, the USA and Canada have been excluded (0.020 ± 0.001%). Taken together, these results suggest a long and largely isolated evolutionary history of PPV‐D in Turkey and further extend knowledge of the diversity of this highly successful strain. The high diversity of PPV‐D in Turkey, together with the basal phylogenetic position of Turkish isolates, are compatible with a hypothesis making Turkey the centre of origin of the D strain.